ASSESSING THE USER EXPERIENCE OF A 360° VIRTUAL REALITY TOUR OF SAMUAN TIGA TEMPLE USING THE UEQ - Iswara, Ida Bagus Ary Indra; Maysaputra, I Putu Angga (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
The virtual reality tour 360° website of Pura Samuan Tiga is a platform with the aim of preserving the cultural assets contained in the cultural heritage site of Pura Samuan Tiga in digital form. With easy access to information, this website is also a medium for delivering cultural information to the wider community. In this study, we want to know the level of user experience experienced by users while using this website. So an evaluation of the user experience of the 360 ° virtual reality tour website of Pura Samuan Tiga was carried out. Measurement using the User Experience Questionnaire (UEQ) method. The evaluation was carried out on respondents totaling 37 data. The results of the UEQ method user experience show a very good assessment. Attractiveness has an average value of 2.28, clarity has a value of 1.95, Efficiency has a value of 2.17, Accuracy has a value of 2.30, Stimulation has a value of 2.48, and Novelty has a value of 2.24. Benchmark analysis of UEQ questionnaire data shows that the user experience of this website is classified as very good with an average value above 2.